PEMBUATAN PROFIL DUKUH SENTONO - Jamalul Lail (UII, 2015)
Sentono is promoted as a center for Agro Techno Park development. For supportthis programm, it is needed to be made profil of village’s development. Profil is made inbook and digital, so the infromation is easy and fast to find.